Multi metal oxide NiO-CdO-ZnO nanocomposite–synthesis, structural, optical, electrical properties and enhanced sunlight driven photocatalytic activity - Munawar, Tauseef; Iqbal, Faisal; Yasmeen, Sadaf; Mahmood, Khalid; Hussain, Altaf (Ceramics international, 2020)
In this article, ternary oxide NiO-CdO-ZnO nanocomposite along with pure NiO, CdO and ZnO were prepared by the homogeneous co-precipitation method. The XRD pattern confirmed the formation of nanocomposite with NiO (cubic)–CdO (cubic)–ZnO (hexagonal). The volume fractions were 38% NiO, 6% CdO and 56% ZnO phase in nanocomposite determined by direct comparison method. Crystallite size and lattice strain were calculated using Scherrer plot, Williamson-Hall and Size-Strain plot methods. The UV–vis was used to study optical properties such as bandgap (Eg), refractive index (n), extinction coefficient (k), optical conductivity (σopt) and dielectric constants (εr, εi). FTIR and Raman analyses have confirmed the successful formation of NiO-CdO-ZnO nanocomposite. The current-voltage measurements revealed that nanocomposite has high electrical response. SEM images shown that nanocomposite has roughly spherical morphology and EDX described that Zn has higher concentration than Ni and Cd. PL spectra of nanocomposite demonstrated the emission bands associated with new energy levels induced by defects. The photocatalytic activity of grown nanocomposite against rhodamine B (RhB) and methylene blue (MB) dyes under sunlight revealed high degradation efficiency 99% for RhB and 98% for MB in 60 and 90 min illumination respectively, indicated that grown nanocomposite is a propitious sunlight-driven photocatalyst to eliminate organic toxins.